2018
DOI: 10.3390/su10072467
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Intra-National Freight Transport: Measurement and Scenarios for Greater Sustainability in Spain

Abstract: Greenhouse Gas (GHG) emissions is a topic of major concern worldwide. Following previous articles which provide a methodology for estimating GHG emissions associated with international trade by transport mode at the world level, in this paper, we estimate an equivalent database of GHG emissions for inter-regional trade flows within a country (Spain). To this end, we built a new database of GHG emissions for origin-destination flows between Spanish provinces during 1995-2015. For each year, we combine industry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A well-functioning seaport, as a link in a sea-land transport chain, may contribute to a modal shift from roads to land-sea transport chains [21,[75][76][77][78][79][80], and can also, by developing a port access policy, change the hinterland transport structure to make it more environmentally friendly, thus contributing to a decrease in transport externalities [81]. Inland shipping is considered to be the most environmentally friendly transport mode when compared to rail or road transport [81,82].…”
Section: Literature Overviewmentioning
confidence: 99%
“…A well-functioning seaport, as a link in a sea-land transport chain, may contribute to a modal shift from roads to land-sea transport chains [21,[75][76][77][78][79][80], and can also, by developing a port access policy, change the hinterland transport structure to make it more environmentally friendly, thus contributing to a decrease in transport externalities [81]. Inland shipping is considered to be the most environmentally friendly transport mode when compared to rail or road transport [81,82].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Specifically, a 10% increase in the interaction TEL*IFT decreases carbon emissions by 3.02%. In the same context, Harris et al (2014) and Llano et al (2018) showed how the use of ICTs for multimodality 6 can decrease carbon emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Santos (2017) recognized the application of short-term tax incentives and subsidizes, and longterm innovation to reduce GHG emissions from road transport. Llano et al (2018) showed the importance of intermodality (road/rail) on environmental sustainability in Spain. Promoting intermodality in freight transport appears (among other options) to be a good solution for more efficient and sustainable transport systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two further contributions take the perspective of practical solution scenarios at the country and sector level, respectively. For Spain, Carlos Llano, Santiago Pérez-Balsalobre and Julian Pérez-García develop scenarios for emission reduction of domestic freight transport [7]. They build up a consistent flow database, develop default emission projections, and study the impacts of a shift of freight from road to railways.…”
Section: Introductionmentioning
confidence: 99%